Legalization of personality scale and preferences for civil servants in Makkah Al-Mukarramah - Al-Bogami, Hussein Ayed (Journal of Educational and Psychological Sciences, 2022)
The study deals with the codification of the personal and professional preference scale (PAPI) on Makkah civil servants, and used the descriptive method and verified the quality of the psychometric characteristics of the personal and professional preference scale (PAPI). the study community was civil servants. the study sample consisted of (300) employees selected by the random cluster sample method. the study found that all the internal consistency coefficients of the sub-scales were acceptable if the number of paragraphs representing each scale was taken into account. The values of the internal consistency coefficients of the subtypes are within acceptable values. All transactions link debugger between the paragraph and the scale to which they belong were positive and the internal consistency affordable real estate, and most of them larger than 0.3 ranged between 0.32 to 0.61 a value indicating internal consistency affordable real estate in terms of need for metrics sub. The results of the exploratory and confirmatory factor analysis showed the saturation of the vertebrae of the PAPI scale on six dimensions plus the dimension of social desirability. The results of the calculation of correlation coefficients between the six factors of the PAPI scale and the five major factors of personality revealed the truthfulness of the concept of the Papi sub-scales and the factors derived therefrom where they corresponded to the expected Model of correlation coefficients with the most famous model of personality (the five major factors of personality model) and also you receive orders; it’s reached For Standards suitable for scale. Among the recommendations of the study the use of the metric in determining the professional preferences of applicants for positions in the Civil Service, and the application of the measure on the candidates for leadership positions from the civil service in Makkah.